2021
DOI: 10.1002/ente.202100189
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Modeling Enhancement of a Solar Desalination Unit with Nanofluids Using Machine Learning Algorithms Integrated with Bayesian Optimization

Abstract: Herein, double slope solar still (DSSS) performance is accurately forecast with the aid of four different machine learning (ML) models, namely, artificial neural network (ANN), random forest (RF), support vector regression (SVR), and linear SVR. Furthermore, the tuning of ML models is optimized using the Bayesian optimization algorithm (BOA) to get the optimal performance of all models and identify the best predictive one. All the models are trained, tested, and validated depending on experimental data acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The model was then measured for accuracy based on the selected statistical indicators: standard error of the regression (S), Durbin-Watson statistic (d), variance inflation factor (VIF), Mallows Cp, probability value (p-value), coefficient of determination (R 2 ), adjusted-R squared (R 2 a ), root mean square error (RMSE), mean absolute error (MAE), and mean absolute percentage error (MAPE). These parameters were calculated using the following equations [17,39,40]:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model was then measured for accuracy based on the selected statistical indicators: standard error of the regression (S), Durbin-Watson statistic (d), variance inflation factor (VIF), Mallows Cp, probability value (p-value), coefficient of determination (R 2 ), adjusted-R squared (R 2 a ), root mean square error (RMSE), mean absolute error (MAE), and mean absolute percentage error (MAPE). These parameters were calculated using the following equations [17,39,40]:…”
Section: Discussionmentioning
confidence: 99%
“…TMY data is considered to be a reliable representation of the weather pattern of Dongji Islet since it is based on the collection of weather data over a long period of time. The multivariable linear regression model, Equation (17), was developed with R-squared (R 2 ), adjusted R-squared (R 2 a ), MAE, RMSE, and MAPE values of 99.5%, 99.4%, 0.144, 0.167, and 9.71%, respectively. This study also showed that the meteorological parameters of daily total global solar radiation, ambient temperature, and extent of cloud cover were the most appropriate variables for predicting the productivity of the prototype solar still.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intelligent methods can be applied for accurate evaluation of these solar stills. Kandeal et al (2021) tested various data-driven methods including ANN, Support Vector Regression (SVR), linear SVR, and RF to model the performance of a doubleslope solar still utilizing the carbon black nanofluid in 1.5% wt concentration. The inputs of the proposed model were air ambient temperature, solar radiation, wind speed, vapor temperature, basin temperature, and temperatures at the glass inlet and outlet.…”
Section: Applications Of Data-driven Methods In Solar Desalinationsmentioning
confidence: 99%